Pengaruh Ketimpangan Gender, Tingkat Partisipasi Angkatan Kerja, dan Kepadatan Penduduk terhadap Pertumbuhan Ekonomi di Indonesia - Okta Adioni Tinokae Rahma Suci (Tapis: Jurnal Penelitian Ilmiah, 2026)
This study aims to analyze the effects of gender inequality, labor force participation rates, and population density on economic growth in Indonesia. The study uses panel data from 34 provinces in Indonesia for the period 2019–2023, obtained from the Central Statistics Agency (BPS). The research method used is multiple linear regression with the Ordinary Least Squares (OLS) approach, analyzed using EViews 12. The results indicate that gender inequality has a significant negative effect on economic growth. Meanwhile, labor force participation rates and population density have a significant positive effect on economic growth in Indonesia. The adjusted R-squared value of 0.9773 indicates that 97.73% of the variation in economic growth can be explained by the independent variables in this study. These findings suggest that reducing gender inequality and increasing labor force participation can support sustainable economic growth in Indonesia.